Asia's Conservative Moment: Understanding the Rise of the Right. Issue 4 (8th August 2018) - Chacko, Priya; Jayasuriya, Kanishka
ABSTRACT: Recent scholarship has identified a new era of post-democracy or democratic crisis in the West, characterised by the increasing resort to authoritarian measures and the erosion of mechanisms such as representative parties and unions that link citizens and social forces with the political process. Conservative political movements, right-wing governments and populism have also emerged in the democratic states of the Asia-Pacific. The existing literature, with its focus on the crisis of social democratic institutions and forms of representative politics, provides inadequate frameworks for explaining these trends in the region. This article suggests that a better way of understanding the emergence of these new forms of political regime in Asia is to locate the origins of democratic crises in processes of global capitalist transformation and political incorporation and disincorporation. The articles in this special issue show that previously dominant modes of incorporation are fracturing under the conditions of neo-liberal capitalist transformation. In the wake of this fracturing, political elites have struggled to created new forms of political incorporation. This has inadvertently resulted in the sharpening of the conditions that give rise to political crisis. The political responses to crises have predominantly been conservative and have led to attempts to restructure the state to limit dissent and electoral competition.